PREPARING GIRLS FOR FAMILY IN KARAKALPAK PEDAGOGY (Academicia Globe: Inderscience Research, 2021)
The article examines the important factors of preparing girls for family life in the Karakalpak pedagogy, measures to overcome the problems of raising girls in the family through the use of the experience of teachers and scientists.